Факторний аналіз фінансового стану корпорацій - Посохов, Ігор Михайлович (Межвузовский центр "Крым", 2013)
У статті проаналізовано історію виникнення та методи факторного аналізу. Запропоновано використовувати метод факторного аналізу, що дозволяє виокремити взаємозалежні фінансові коефіцієнти, як складовий елемент методики оцінки фінансового стану корпорацій. Фінансові ризики є найбільш загрозливими для успішного функціонування та розвитку корпорацій, тому їх оцінка дозволить підвищити ефективність прогнозування та управління ризиками корпорацій.

At present the actual problem of sustainable economic development of Ukraine. Sustainable development of the national economy is not possible without effective control by domestic corporations implementation of risk management in corporations, which requires accurate risk assessment of modern corporations. Financial risks are the most dangerous for the successful operation and development corporations, so their score will increase the efficiency of forecasting and risk management corporations. Assessment of financial risks is performed by evaluating the financial condition of corporations. The urgency of this problem and practical value influenced the choice of research topic. The development of the ideas of factor analysis in psychology researchers engaged in the following: L. Turnstone, C. Spearmen, R. Cattell. Mathematical factor analysis investigated Kaiser, Turnstone, Tucker, Harman, Hotelling, and other scientists. The aim of paper is to study the use of factor analysis to assess the financial condition of companies. The study on the assessment of financial risk by evaluating the financial condition of corporations using factor analysis shows the effectiveness of the method of factor analysis as part of the methodology for assessing the financial condition of corporations and allows accurate assessment of the financial risks of the corporation.
Keywords: ризики; корпорація; фінансовий ризик; оцінка фінансового стану; оцінка фінансових ризиків; risk; corporation; financial risk assessment